1972
DOI: 10.1055/s-0038-1649372
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Induction of Cryofibrinogen and “Paracoagulation” by Reptilase

Abstract: SummarySmall doses of Reptilase, a snake venom enzyme which exclusively liberates fibrinopeptide A from fibrinogen, leads to formation of cryofibrinogen as well as ethanol- and protamine-precipitability of plasma both in vitro and in vivo. Precipitates obtained in vitro were shown to contain both fibrinogen and fibrin monomer. At 20° C Reptilase-treated fibrinogen solutions contained complexes with a sedimentation rate of 11-11.6 s20W, similar to those observed after thrombin. The artificial production of cryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1973
1973
1987
1987

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…This was also found by other investigators [5], In the isolated perfused pig ear, batroxo bin at a concentration of 0.25 BU/ml perfu sion solution caused a release of fibrinolytic activity which was suppressed by the addi tion of IgG antibodies against human v-PA (table I). The activator release increased in a dose-dependent manner up to 1 BU batroxobin/ml (table II).…”
Section: Resultssupporting
confidence: 83%
“…This was also found by other investigators [5], In the isolated perfused pig ear, batroxo bin at a concentration of 0.25 BU/ml perfu sion solution caused a release of fibrinolytic activity which was suppressed by the addi tion of IgG antibodies against human v-PA (table I). The activator release increased in a dose-dependent manner up to 1 BU batroxobin/ml (table II).…”
Section: Resultssupporting
confidence: 83%
“…It was also shown that cryofibrinogen can be produced in normal plasma after the addition of thrombin or thrombin-like enzymes or in animals following the infusion of agents that induce fibrin formation. These observations, as well as the deter mination of the fibrinopeptides content of such precipitates, demonstrated that cryofibrinogen is a complex of fibrinogen with fibrin-lacking fibrino-peptides A (3,16,17). Later it was shown that the cryofibrinogen of a patient with DIC contained, in addition to fibrinogen, a nonclottable com ponent which was identified as cold-insoluble globulin (CIg), currently known as fib'ronectin (10).…”
Section: Introductionmentioning
confidence: 99%